Lipoproteins of Haemophilus influenzae type b. - Weinberg, G A (1988)
Haemophilus influenzae type b Minn A produced 12 lipoproteins with apparent molecular weights of between 14,000 and 67,000. The lipoproteins were identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and fluorography of delipidated extracts of cells grown in [3H]palmitate. When the delipidated cell extracts were subjected to acid methanolysis, tritium was quantitatively recovered as palmitate and methyl palmitate, indicating that the [3H]palmitate had not been degraded and reincorporated into nonlipid material during cell growth. One of the lipoproteins comigrated with outer membrane protein (OMP) P6. OMP P6 was purified from [3H]palmitate-labeled cells. The purified protein preparation contained both amide- and ester-linked fatty acids. We conclude that (i) H. influenzae type b produces several lipoproteins, and (ii) one of these lipoproteins is OMP P6, a protein under consideration as a vaccine component.